2019
DOI: 10.1002/qua.25918
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical scrutinization of nine benzoic acid dimers: Stability and energy decomposition analysis

Abstract: Aromatic carboxylic acids are able to form diverse dimers and multimers due to their hydrogen bond donor and acceptor cites, as well as the aromatic rings. In this work, we examine nine benzoic acid dimers stabilized by hydrogen bonding and stacking interactions. Interacting quantum atoms methodology revealed that dominant attractive interactions in all of them, including hydrogen bonded systems, are due to exchange-correlation. Coulomb interactions are significant only in the most stable dimer with a double h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The COOH group of BA slightly turns away from the plane of the benzene ring while the H1-OH bond is elongated. As for TF configuration in vacuum, the H1-O (in the -CH 2 OH group of β-CD) bond length is 1.847 Å, which is quite close to the hydrogen bond lengths in the BA-BA dimer structure (1.66–1.83 Å) [ 18 ]. In this case, the charge transfer from β-CD to the BA molecule is remarkable compared to that in the presence of solvents.…”
Section: Resultsmentioning
confidence: 72%
“…The COOH group of BA slightly turns away from the plane of the benzene ring while the H1-OH bond is elongated. As for TF configuration in vacuum, the H1-O (in the -CH 2 OH group of β-CD) bond length is 1.847 Å, which is quite close to the hydrogen bond lengths in the BA-BA dimer structure (1.66–1.83 Å) [ 18 ]. In this case, the charge transfer from β-CD to the BA molecule is remarkable compared to that in the presence of solvents.…”
Section: Resultsmentioning
confidence: 72%
“…It has been demonstrated that M06-2X functional successfully describes charged particles, 36,49,50 but also systems with various types of interactions. 31,39,51–57 IQA analysis was performed with the AIMAll software 58 by employing the promega5 basin integration method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…For this purpose, the Interacting Quantum Atoms methodology 21,22 (IQA) was employed, which has so far been successfully utilized for analysis of diverse systems, properties and processes. 23–41 It enables quantification of classical and non-classical interaction terms among selected fragments (the fragments being BN & PCH + , BN & H + , PC & H + , or BN & H + & PC), but also energetical properties of the fragments themselves when their geometry and the environment modify upon reaction advancement. The paper is organized as follows: Section 2 contains details of the computational procedure; the results and their discussion are presented in Section 3; the conclusions are summarized in Section 4.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we employed the interacting quantum fragments approach to study two systems: reaction between hydroquinone and methoxy radical (HQM) 82 as well as interaction between benzoic acid molecules in benzoic acid dimers (BD). 83 The largest deviation of IQA energy from SCF energy in the former case amounts to 1 kJ/mol and in the latter to 2 kJ/mol. However, HQM and BD contain 19 and 30 atoms, respectively, which lead to 19 × (19 − 1)/2 = 171 and 30 × (30 − 1)/2 = 435 pair interactions.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…The effect of larger charges of alkaline earth cations compared to the alkali counterparts should also not be neglected. In the current contribution, we studied interactions among different fragments in guanine quartets and their complexes with alkali (Li + , Na + , K + ) and alkaline earth cations (Be 2+ , Mg 2+ , Ca 2+ ) in the gas phase using the interacting quantum atoms (IQA) methodology, which enabled understanding of cations’ nature on hydrogen bond cooperativity in guanine quartets. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%